2022
DOI: 10.1002/pep2.24289
|View full text |Cite|
|
Sign up to set email alerts
|

Current peptide vaccine and immunotherapy approaches against Alzheimer's disease

Abstract: Peptide vaccines and immunotherapies against aggregating proteins involved in the pathogenesis and progression of Alzheimer's disease (AD)-the β-amyloid peptide (Aβ) and tau-are promising therapeutic avenues against AD. Two decades of effort has led to the controversial United States Food and Drug Administration (FDA) approval of the monoclonal antibody Aducanumab (Aduhelm), which has subsequentially sparked the revival and expedited review of promising monoclonal antibody immunotherapies that target Aβ. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Donanemab, another humanized mAb from Eli Lilly & Co., recognizing Aβ(p3-42) a pyroglutamate form of Aβ that is aggregated in amyloid plaques [ 63 , 64 , 65 ]. This humanized IgG1 antibody is currently being tested on AD patients with prodromal to moderate AD in a phase III clinical trial [ 66 , 67 ].…”
Section: Current Treatment Strategies Targeting Aβmentioning
confidence: 99%
“…Donanemab, another humanized mAb from Eli Lilly & Co., recognizing Aβ(p3-42) a pyroglutamate form of Aβ that is aggregated in amyloid plaques [ 63 , 64 , 65 ]. This humanized IgG1 antibody is currently being tested on AD patients with prodromal to moderate AD in a phase III clinical trial [ 66 , 67 ].…”
Section: Current Treatment Strategies Targeting Aβmentioning
confidence: 99%
“…Another point to consider in forthcoming research relies on the fact that, even though the use of monoclonal antibodies as passive immunization against misfolded toxic proteins has been shown to be a suitable strategy for the treatment of NDDs (e.g., AD-related monoclonal antibodies: Aducanumab, Gantenerumab, Solanezumab, and Crenezumab) [ 152 , 153 , 154 , 155 ], plant-based expression systems have not yet been exploited for the production of these antibodies. Remarkably, emerging technologies have made it possible to obtain antibody production yields in whole plants of up to 2 g per kg of fresh weight [ 156 ], which portends a profitable future for the entry of this type of pharmaceutical product to the market.…”
Section: Future Directionsmentioning
confidence: 99%
“…Accumulating evidence suggests these monoclonal antibodies can potentially prevent tau’s cell-to-cell propagation and aggregation [ 65 ]. Janssen Research and Development ran two clinical trials in phase 1 to evaluate its safety and tolerability in participants [ 66 ]. The 2017 phase I clinical trial reported the monoclonal antibody to be safe and well tolerated [ 66 ].…”
Section: Tau Immunotherapiesmentioning
confidence: 99%
“…Janssen Research and Development ran two clinical trials in phase 1 to evaluate its safety and tolerability in participants [ 66 ]. The 2017 phase I clinical trial reported the monoclonal antibody to be safe and well tolerated [ 66 ]. In 2019, a phase I clinical trial reported dose-dependent increases in exposures.…”
Section: Tau Immunotherapiesmentioning
confidence: 99%